Effect of slaughter age on fattening performance and carcass characteristics of Japanese quails (Coturnix coturnix japonica) - Seker, I.; Bayraktar, M.; Kul, S.; Ozmen, O. (Garuda Scientific Publications, 2007)
To determine the most economic slaughter age for male Japanese quails a total of 220 quail chicks were fed a standard feed up to 49 days. Rate of live weight gain started decreasing after 28 days of age. Feed consumption showed similar trend after d35. However, the feed required for each gram of weight gain exhibited steep increase after d42. Dressing percentage was the highest when the birds were slaughtered on d35. Considering these results the slaughter of male Japanese quails is recommended at 42 days of age.
Keywords: fattening performance; carcass; slaughter age; quail